The impact of predominant reliance on non – interest income on sustainable bank performance: case study of Barclays bank of Zimbabwe - Kashiri, Munyaradzi (Midlands State University, 2017)
The aim of this research was to analyse the impact of non – interest income on the financial performance of banking institutions in Zimbabwe. The researcher adopted both quantitative and qualitative methods of research to gather data. Likert Scale based questionnaires were distributed to a stratified sample of 26 individuals out of a total population of 35. 3 interviews were also carried out in addition to questionnaires to maximize the effectiveness of the research. More so, the ordinary least squares (OLS) regression test was carried out by use of the EVIEWS statistical package. The result of the regression test showed a positive relationship between non – interest income and bank profitability in Zimbabwe. The increase in a bank’s non – interest income actually results in an increase in its profitability level ceteris paribus. It was discovered that the business of non – interest income maximises risk exposure for banks, however, operating costs need to be watched carefully when conducting the business of generating non – interest income because such activities were discovered to be the major drivers of bank operating costs. Inflation, risk policies, political stability and bank strategy were found to be other determinants of bank performance in spite of non – interest income. The researcher recommended that banks should broaden streams from which transaction based income is earned since it is the major source of non – interest income. Over and above, the researcher established that banks need to depend more on the business of non – interest income more than interest income since the research showed a positive relationship between non – interest income and bank profitability.